1989
DOI: 10.1101/gad.3.11.1745
|View full text |Cite
|
Sign up to set email alerts
|

Novel phytochrome sequences in Arabidopsis thaliana: structure, evolution, and differential expression of a plant regulatory photoreceptor family.

Abstract: Phytochrome is a plant regulatory photoreceptor that mediates red light effects on a wide variety of physiological and molecular responses. DNA blot analysis indicates that the Arabidopsis thaliana genome contains four to five phytochrome-related gene sequences. We have isolated and sequenced cDNA clones corresponding to three of these genes and have deduced the amino acid sequence of the full-length polypeptide encoded in each case. One of these proteins ipbyA) shows 65-80% amino acid sequence identity with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
683
1
6

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 798 publications
(712 citation statements)
references
References 52 publications
22
683
1
6
Order By: Relevance
“…To explore this hypothesis, we used a genetic approach to test whether phytochrome activity is required for SD axillary flower formation. There are at least five phytochrome genes in Arabidopsis (PHYA to PHYE; Sharrock and Quail, 1989;Clack et al, 1994). The activities of all five genes are strongly suppressed by the hy7 mutation that blocks phytochrome chromophore biosynthesis (Parks and Quail, 1991).…”
Section: Control Of Ap2-7 Axillary Flower Production By Phytochromementioning
confidence: 99%
“…To explore this hypothesis, we used a genetic approach to test whether phytochrome activity is required for SD axillary flower formation. There are at least five phytochrome genes in Arabidopsis (PHYA to PHYE; Sharrock and Quail, 1989;Clack et al, 1994). The activities of all five genes are strongly suppressed by the hy7 mutation that blocks phytochrome chromophore biosynthesis (Parks and Quail, 1991).…”
Section: Control Of Ap2-7 Axillary Flower Production By Phytochromementioning
confidence: 99%
“…Phytochromes are soluble chromoproteins that convert photoreversibly between two spectrally distinct forms when sequentially absorbing red (R) and far-red (FR) light, and this interconversion occurs immediately both in vivo and in vitro (Butler et al, 1959). Phytochromes are encoded by a small gene family (phytochrome genes PHYA to PHYE in Arabidopsis; Sharrock and Quail, 1989;Clack et al, 1994). Studies with mutants deficient in specific phytochromes have shown that phytochrome A (PhyA) and phytochrome B (PhyB) have distinct action spectra for the photoinduction of seed germination (Shinomura et al, 1996) and distinct fluence and wavelength requirements for expression of the chlorophyll a / b binding protein gene ( CAB ) (Hamazato et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Active Pfr form can be converted back to the inactive Pr form by absorption of specific far-red light (9,10). The model plant, Arabidopsis thaliana, contains five genes (PHYA to PHYE) that encode phytochrome apoproteins (11,12). Phytochromes are classified as light labile phytochrome A (phyA) and light stable phytochromes B E (phyB-phyE) (13).…”
mentioning
confidence: 99%